2014
DOI: 10.1111/bjd.12641
|View full text |Cite
|
Sign up to set email alerts
|

High expression of FOXP3 in primary melanoma is associated with tumour progression

Abstract: High expression of FOXP3 in the primary melanoma may be used as an additional independent prognostic marker for early tumour progression in patients with melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 27 publications
3
56
0
1
Order By: Relevance
“…Their link with clinical prognosis has been reported in a variety of human solid tumors. The majority of these studies report that an extensive infiltration with DC is associated with increased OS and cover many tumors types, including melanoma (Gerber et al, 2014;Ladányi et al, 2007;Neagu et al, 2013;Simonetti et al, 2007), HCC (Cai et al, 2006;Yin et al, 2003), gallbladder (Furihata et al, 2005;Nakakubo et al, 2003), oral (Reichert et al, 2001), esophageal (Furihata et al, 1992;Ishigami et al, 2003a;Lu et al, 2013), gastric (Amoueian et al, 2015Ananiev et al, 2011;Kashimura et al, 2012;Tsukayama et al, 2005), NSCLC (Al-Shibli et al, 2009;Dai et al, 2010;Hald et al, 2013;Inoshima et al, 2002;Johnson et al, 2000), colorectal (Gulubova et al, 2012;McMullen et al, 2010;Nakayama et al, 2003;Väyrynen et al, 2014), bladder (Inoue et al, 1993), breast (Iwamoto et al, 2003;La Rocca et al, 2008;Lespagnard et al, 1999;Park et al, 2012), endometrial (Honig et al, 2005;Lijun et al, 2012), and ovarian cancer (Eisenthal et al, 2001;Zhang et al, 2015). Nevertheless, the infiltration with CD123 + plasmacytoid DC has been associated with shorter OS in breast cancer ( Jensen et al, 2012;Treilleux et al, 2004), as well as the presence of CD208 + and CD1a + DCs in colorectal (Sandel et al, 2005)...…”
Section: Role Of Dcsmentioning
confidence: 99%
“…Their link with clinical prognosis has been reported in a variety of human solid tumors. The majority of these studies report that an extensive infiltration with DC is associated with increased OS and cover many tumors types, including melanoma (Gerber et al, 2014;Ladányi et al, 2007;Neagu et al, 2013;Simonetti et al, 2007), HCC (Cai et al, 2006;Yin et al, 2003), gallbladder (Furihata et al, 2005;Nakakubo et al, 2003), oral (Reichert et al, 2001), esophageal (Furihata et al, 1992;Ishigami et al, 2003a;Lu et al, 2013), gastric (Amoueian et al, 2015Ananiev et al, 2011;Kashimura et al, 2012;Tsukayama et al, 2005), NSCLC (Al-Shibli et al, 2009;Dai et al, 2010;Hald et al, 2013;Inoshima et al, 2002;Johnson et al, 2000), colorectal (Gulubova et al, 2012;McMullen et al, 2010;Nakayama et al, 2003;Väyrynen et al, 2014), bladder (Inoue et al, 1993), breast (Iwamoto et al, 2003;La Rocca et al, 2008;Lespagnard et al, 1999;Park et al, 2012), endometrial (Honig et al, 2005;Lijun et al, 2012), and ovarian cancer (Eisenthal et al, 2001;Zhang et al, 2015). Nevertheless, the infiltration with CD123 + plasmacytoid DC has been associated with shorter OS in breast cancer ( Jensen et al, 2012;Treilleux et al, 2004), as well as the presence of CD208 + and CD1a + DCs in colorectal (Sandel et al, 2005)...…”
Section: Role Of Dcsmentioning
confidence: 99%
“…In humans, Tregs are highly enriched in many solid tumors, including primary melanoma (3,4), invaded lymph nodes (5), and metastatic melanoma (MM) (4)(5)(6). High-frequency Tregs correlate with tumor progression and poor survival in many solid tumors, including melanoma (7), and have been associated with poor clinical outcome in melanoma patients (MPs) treated with immunotherapy (8). Tregs encompass multiple T cell subsets that control immunity through a variety of mechanisms depending on various environmental cues.…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming clear that FOXP3 plays an important role in controlling the expression of numerous genes involved in cancer development in the epithelium [17-20]. However, the effects of FOXP3 on cancer are very controversial, such as its roles in breast, ovarian, esophageal, and cervical cancer [13, 15, 17, 21-24]. Zhang and Sun demonstrated that FOXP3 is able to significantly reduce the migration and invasion capability of malignant ovarian cells [15].…”
Section: Introductionmentioning
confidence: 99%